Pembelajaran Pendidikan Jasmani Olahraga Kesehatan (Pjok): Bagaimanakah Tingkat Motivasi Belajar Siswa - Muhammad Farel; Oki Candra (Journal on Education, 2024)
The purpose of this research is to see the level of student learning motivation in class VIII PJOK learning at SMP Negeri 4 Siak Hulu. Based on the results of observations of class VIII students at SMP Negeri 4 Siak Hulu, it was found that there was a lack of student enthusiasm in participating in physical activities and sports in PJOK learning. teachers in motivating students or providing positive encouragement related to PJOK learning, The presence of students with low levels of motivation can be an indicator of problems that need to be addressed, Physical environmental conditions, such as inadequate sports facilities, may influence the level of student motivation to learn, and Low level of awareness students about the importance of a healthy lifestyle and physical fitness can be a problem, resulting in a lack of motivation to participate in PJOK activities. The test used in this research used a questionnaire or questionnaire with a Likert scale. The sample in this study was 130 class VIII students at SMP Negeri 4 Siak Hulu. From the results found in the field regarding the level of student learning motivation in class VIII PJOK learning, the result was 59.73% classified as "Enough" with a percentage between 40% - 60%.